PENGARUH PEER SUPPORT TERHADAP KUNJUNGAN LANSIA HIPERTENSI DI POSYANDU LANSIA KRAJAN BARAT DESA SUMBERJATI LUMAJANG - Tiwik Suryanti; Ana Fitria Nusantara; Alwin Widhiyanto (NHM PRESS, 2023)
Elderly visits to elderly integrated service posts are a form of health behavior. By making regular visits the elderly can find out their health developments periodically against the threats of health problems they face (early detection), motivation is one of the factors that influence the regularity of elderly visits to service posts integrated. The purpose of this study was to determine the effect of peer support on visits to elderly hypertensives at the Posyandu for the elderly Krajan Barat, Sumberjati Lumajang village. The design of this study was a pre- experimental design with a One-group Pre test-Post test Research Design. The population of this study were all elderly hypertensives in the West Krajan elderly posyandu, Sumberjati village, Tempeh Lumajang with a sample of 41 respondents who were taken by porporsive sampling. Data were collected through observation sheets and analyzed using paired samples T-Test. The results showed that 9 respondents (22%) attended the elderly Posyandu before Peer Support and 32 respondents (78%) did not attend. After peer support support were 40 respondents (97.6%) and 1 respondent (2.4%) was absent. The results of the analysis test using the paired samples test showed a value of p = 0.000 with a significant level of 0.05 (p value <0.05), which means that there was an influence between peer support on visits to elderly hypertensives at the Posyandu for the elderly in Krajan Barat village, Sumberjati Lumajang. This happens because Peer Support can provide a sense of comfort, a feeling of being loved and cared for by fellow elderly so that they become part of the extended family of the elderly. Therefore, Peer Support can be developed for other programs, especially health programs whose achievements are low due to the influence of certain factors.